2014
DOI: 10.3389/fpls.2014.00383
|View full text |Cite
|
Sign up to set email alerts
|

Tombusvirus-yeast interactions identify conserved cell-intrinsic viral restriction factors

Abstract: To combat viral infections, plants possess innate and adaptive immune pathways, such as RNA silencing, R gene and recessive gene-mediated resistance mechanisms. However, it is likely that additional cell-intrinsic restriction factors (CIRF) are also involved in limiting plant virus replication. This review discusses novel CIRFs with antiviral functions, many of them RNA-binding proteins or affecting the RNA binding activities of viral replication proteins. The CIRFs against tombusviruses have been identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 114 publications
0
18
0
Order By: Relevance
“…In this yeast experimental system, cells are transformed to express the tombusviral p33 and p92 replication proteins, which function to replicate short tombusvirus replicons derived from viral defective interfering RNAs. Studies involving genome wide screens and yeast protoarrays revealed a subset of host factors associated with the viral replication machinery [32,33,34]. Homologues of many identified factors that have been identified in plants and investigations typically report parallel analysis of protein contributions to virus replication in yeast and in plants.…”
Section: Ubiquitin Proteasome System Supporting Virus Replication mentioning
confidence: 99%
“…In this yeast experimental system, cells are transformed to express the tombusviral p33 and p92 replication proteins, which function to replicate short tombusvirus replicons derived from viral defective interfering RNAs. Studies involving genome wide screens and yeast protoarrays revealed a subset of host factors associated with the viral replication machinery [32,33,34]. Homologues of many identified factors that have been identified in plants and investigations typically report parallel analysis of protein contributions to virus replication in yeast and in plants.…”
Section: Ubiquitin Proteasome System Supporting Virus Replication mentioning
confidence: 99%
“…However, some cellular factors could act as CIRFs restricting virus replication (22,83,84). Among the several CIRFs against tombusviruses, Rsp5p and the WW-domain proteins are strong inhibitors, which are present in both yeast and plant cells (64,65).…”
Section: Rsp5p and Ww-domain Proteins Act As Cirfs Against Tombusvirumentioning
confidence: 99%
“…In addition to the WW-domain-containing host factors, other cellular factors with CIRF functions might also be involved in regulation of TBSV replication (22). To further test the possible regulatory functions of recruited cellular proteins, we chose two additional cellular CIRF factors that inhibit TBSV replication.…”
Section: Inhibition Of the Rna-binding And Protein-interaction Functimentioning
confidence: 99%
See 2 more Smart Citations